Konsep Pendidikan Akhlak Bagi Anak Didik Menurut Imam Buhanul Islam Az-Zarnuji dalam Kitab Ta’limul Muta’allim - Amin, Muhammad (Seutia Hukamaa Cendekia, 2024)
This study intends to investigate the concept of moral education for students as it is presented in the book of ta'limul muta'allim and determine whether it applies to students today. The research method utilized is library research, which involves consultation of pertinent material. The findings of the study are as follows: 1) The components of the concept of moral education for children that are included in the book of ta'limul muta'allim are straightening out intentions when learning, learning how to choose knowledge, teachers, friends, and peaking in steadfastness, glorifying knowledge and knowledgeable people, being serious, maintaining continuity, being enthusiastic about learning, and using tawakkal and wara' when pursuing knowledge. 2) The significance of moral education in the book that includes the book of ta'limul muta'allim It is both intellectual education and moral education being provided to today's pupils. Imam Az-zarnuji's focus on these two characteristics may be a solution to the current scenario in the world of education, which is experiencing a crisis of morality and places only an emphasis on the intellectual side. As far as he is concerned, the purpose of education is not merely to generate a good human being at birth; rather, Imam Az-zarnuji desires a knowledgeable person to be good in both his heart and his actions. The process of seeking information is the most important thing, and successful outcomes are an award for someone pursuing knowledge of something.